Considerations for Optimal Grafting in Rhinoplasty - Dermody, Sarah M.; Lindsay, Robin W.; Justicz, Natalie (Facial Plastic Surgery, 2023)
A wide variety of grafting materials and techniques can be used to create functional and aesthetic changes in rhinoplasty. Choosing the optimal grafting approach is critical to achieving an optimal patient outcome. We present a review of autografts, allografts, and alloplasts used in primary and revision rhinoplasty and discuss factors that impact graft choice. Autologous grafts serve as the pillar for grafting material in rhinoplasty given their reliable long-term outcomes, low rates of infection, resorption, and extrusion, and ability to provide structural scaffolding as well as contour. Cadaveric allografts can be utilized as a source of grafting material in certain clinical scenarios including revision rhinoplasty and have been shown to be equally safe and effective as autologous grafts while avoiding donor-site morbidity. Alloplasts can prove useful in rhinoplasty in cases of iatrogenic nasal deformities or revision cases. Careful consideration of clinical scenario, patient factors, and outcome goals is necessary to choose the appropriate grafting approach to address functional and cosmetic outcomes.
Keywords: rhinoplasty; grafting; autograft; costal cartilage; allograft